Strategi Implementasi Keselamatan dan Kesehatan Kerja (K3) di Pelaku UMKM Pembuatan Minyak Gaharu Lubuk Begalung Padang Sumatera Barat - Fatchurrohman, Nanang; Farid, Mohammad; Yenni, Zefri; Dewi, Alfita (LPPM Universitas Dharma Andalas, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) engaged in agarwood oil production in Lubuk Begalung, Padang, West Sumatra, represent a type of natural resource-based business that involves a relatively high level of occupational risk. These risks primarily arise during the extraction and processing stages of agarwood, which involve high-temperature operations, pressurized processing equipment, and potential exposure to chemical substances. Preliminary observations conducted by the community service team revealed that business owners lack sufficient understanding and implementation of Occupational Health and Safety (OHS) principles. This condition poses a significant threat of workplace accidents, reduces productivity, and may disrupt the continuity of business operations. To address this issue, the community engagement team implemented a structured OHS program comprising three key components: the introduction and use of personal protective equipment (PPE), the enforcement of safe work procedures, and the cultivation of a healthy and safe workplace culture. This initiative was designed using a participatory approach to ensure that it would be easily understood and adopted by MSME stakeholders. The results of the program indicate a marked increase in awareness and adherence among business operators regarding personal protection and workplace safety during operational activities. Through this implementation, it is expected that a safer, more comfortable, and productive work environment will be established, thereby supporting the sustainability of the agarwood oil production business.